The Brokenwood mysteries. Series 10 [videorecording (DVD)] - Rea, Neill, 1971-; Sutherland, Fern; Rawiri, Jarod; Ionda, Cristina (Acorn TV, 2024)
From a brutal murder with a Jurassic twist to a spooky crime scene on the Day of the Dead, Brokenwood's alarming murder rate continues to keep detectives Shepherd, Sims, and Chalmers busy.